PREPARATION AND EVALUATION OF A MILK DESSERT WITH ORANGE FIBER - MARTÍNEZ A., Olga L.; ROMÁN M., María O.; GUTIÉRREZ E., Ester L.; MEDINA M., Gilma B.; CADAVID C., Margarita; FLÓREZ A., Óscar A. (Vitae, 2009)
The consumption of dietary fiber has been associated with functional food properties which improves people’s intestinal health. It also contributes towards the prevention of colon cancer, cardiovascular diseases, and weight control. The purpose of this study is to prepare and evaluate a milk dessert added with fiber from residues resulting from orange pulp separation. Orange fiber is selected as a raw material to prepare desserts because orange is a good source of soluble and insoluble dietary fiber and besides in the sensorial characterization made by trained judges, it was found that this fiber has odor and aroma of the fruit –the orange– and pleasant textural mouth characteristics. Proximal analysis shows that orange fiber has 59.1 % of total dietary fiber, and the soluble fraction is 27.5 %, with a good content of iron, phosphorus, and other nutrients, except for raw grease. From the technological point of view, it is feasible to incorporate until 5.0 % of orange fiber in the milk dessert, which presents 2.1 % of milk fat, 7.3 of milk solids, and a 25.3 % of total solids. The taste profile shows that the dessert with orange fiber has a medium sensorial quality. Taste describers of this product are: orange, citric, sour, sweet, cooked, and with a residual bitter flavor. Texture describers perceived are: humid, soft, masticable, and fibrous. This new food contributes with its own nutrients and with an additional quantity of fibers which make it a healthy food and are a pleasant, simple, and economic alternative, so people can increase their daily intake of dietary fiber. Besides, through the use of residues in orange transformation, environmental pollution can be decreased.